Effect of Hydrolyzing Enzymes on Wheat Bran Cell Wall Integrity and Protein Solubility. Issue 2 (19th October 2015) - Arte, Elisa; Katina, Kati; Holopainen‐Mantila, Ulla; Nordlund, Emilia
Abstract : Wheat bran contains good quality protein, but given its location inside aleurone cells, this protein has restricted digestibility. The aim of this work was to liberate and solubilize wheat bran proteins via cell wall degradation by using carbohydrate‐hydrolyzing and proteolytic enzymes without causing extensive protein hydrolysis. Bran incubated with water (without added enzymes) for 16 h increased the solubilized organic nitrogen content from 14.0 to 42.8%. Enzymes with solely carbohydrate‐hydrolyzing activity increased the water‐soluble pentosan and reducing sugar contents but did not significantly increase protein solubilization or protein release from the aleurone cells. Enzymes with proteolytic activity significantly increased the solubilization of protein to 58.2% already at 4 h. Significant protein hydrolysis was detected with a high dosage of protease. However, based on light microscopy, the enzymatic treatment mainly modified the proteins in the subaleurone layer, and it was less effective on proteins inside the aleurone cells. With optimized protease treatment (3 h, 35°C, and 550 nkat/g), effective protein solubilization (>48%) without extensive protein hydrolysis (free amino nitrogen content <45 mg/L) was achieved. In conclusion, intensive solubilization of proteins in the subaleurone layer of wheat bran is possible by using exogenous enzymes with proteolytic activities.